Characteristics and risk factors for high fasting blood glucose among managers and government officials in the Philippines - Patalen, Chona F.; Guinto, Sarah E.; Atrero, Cristilyn T.; Ducay, Apple Joy D.; Duante, Charmaine A.; Capanzana, Mario V. (2018)
Diabetes ranks fifth among the top causes of mortality in the Philippines. In the 2013 National Nutrition Survey (NNS), prevalence of high fasting blood glucose (FBG) was highest among government officials and managers (10.3%) compared to all other occupation groups. Thus, the study aimed to determine the association between socio-demographic characteristics and selected non-communicable disease (NCD) risk factors with the prevalence of high FBG among government officials, executives, managers, supervisors, and proprietors in the Philippines. The study was a cross-sectional analysis of the 2013 NNS using a multi-stage stratified sampling design. Filipinos – 20 years old and above working as managers of any enterprise, government office and other organizations, with data on FBG and other NCD risk factors – were included in the study. Descriptive statistics were generated using Stata version 12.0. Simple logistic regression was used to determine the association of NCD risk factors with high FBG. Result showed that in this occupation group, factors such as age (≥40 years old), elevated blood pressure (≥140/90 mmHg) and triglyceride level (≥150 mg/dL), family history of diabetes, BMI of >25 kg/m2, high waist circumference and waist-hip ratio, and currently drinking alcoholic beverages were associated with high FBG. No significant relationship was observed between sex, educational background, HDL-cholesterol level, smoking status, fruit and vegetable consumption, and physical activity with high FBG. This study identified a high prevalence of high FBG among managers in the Philippines and the risk factors that are significantly associated with this condition. Interventions in the workplace to prevent and control high FBG and diabetes through early diagnosis and risk management, treatment, and explicit health policies should be initiated.
Keywords: Diabetes; Diabetes prevention; Diabetes risk factors